Islamic Finance : Opportunities, Challenges, and Policy Options - Kammer, Alfred; Norat, Mohamed; Pinon, Marco; Prasad, Ananthakrishnan (Washington, D.C. : International Monetary Fund, 2015)
The SDN discusses the main policy issues and challenges in building an inclusive and safe Islamic finance industry, with emphasis on Islamic banking and Sukuk markets. To this end, it discuses why Islamic finance matters, taking into account its recent and prospective growth; and, its potential contributions in terms of financial inclusion, support for small- and medium-sized enterprises and investment in public infrastructure and, in principle, reduced systemic risk. It then covers a range of regulatory and other challenges, and offers policy advice, to address factors that hamper the development of the industry and, more generally, the delivery of its potential benefits. The paper covers regulatory and supervisory issues, safety nets and resolution frameworks, access to finance, Sukuk markets, and macroeconomic policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet